Group-living decrease predation risk of individual: Evidence from behavior, hormones and reproduction of plateau pika - Zhou, Rui; Hua, Rui; Tang, Zhuangsheng; Hua, Limin (Frontiers in Ecology and Evolution, 2023)
Extensive research confirms that abiotic stressors like predation risk can profoundly affect animal condition. However, there is a lack of experimental research assessing the suite of physiological responses to risk. We increased predation risk in free-living plateau pikas (Ochotona curzoniae) by simulating natural chases using a model predator (UAV: unmanned aerial vehicle) and monitored behavior, physiology, and reproduction of pikas. We found that: Predation risk affects the body weight of plateau pika under different population density stress, but the effect is not significant. Compared with the non-predation risk treatment (control), the plateau pika under high population density stress mainly responded to the risk of predation by reducing the foraging time and increasing the vigilance time, while plateau pikas under low population density pressure not only reduce foraging time and appropriately increase vigilance time, but also focus on increasing the concealing time in the burrows. The corticosterone (CORT), cortisol and thyroid (T4) level of plateau pika with low population density under the predation risk was significantly higher than those in the control, and the testosterone (T), progesterone (PROG), leptin (LEP) and testicular weight of plateau pika with low population density in the predation risk was significantly lower than those in the control. There was no difference in the litter size of female pika between predation risk treatments and control. Broadly, our result show that predation risk had significant effects on the behavior, physiology and reproduction of plateau pikas with low population density, but had no significant effect with high population density, and the response of male plateau pika to predation risk was greater than that of female. Therefore, the prevention of plateau pika should focus on the control of population density and the protection of predators, so as to avoid the failure of ecological prevention methods such as natural enemies due to the increase of population density.